An Appraisal on the Potential uses of Bentonite and its Availability and Exploitation in Kenya - Mutisya, Peter K.; Maranga, SM; Ikua, Bernard W (My University, 2022)
— Bentonite is a smectite clay formed from the alteration of siliceous, glass-rich volcanic rocks such as tuffs and ash deposits. The major mineral in bentonite is montmorillonite, which is a hydrated sodium, calcium, magnesium or aluminum silicate, or a combination of these. The industrial bentonites are generally either the sodium or calcium variety. Bentonites are important and essential in a wide range of applications including well drilling, foundry sand binding, iron ore pelletizing, pet waste absorbents, and civil engineering uses such as waterproofing and sealing. In many developing countries, local bentonite producers provide the livelihood for many marginalized workers. This paper presents the many economic uses to which bentonite can be put. In addition, the paper gives highlight on the numerous opportunities for investment in which bentonite is key. Special focus is given on the use of bentonite in deep drilling and foundry which together use the largest quantity of bentonite in the world.
Keywords: Bentonite; Foundry; Industrial minerals; Well drilling